TEORIA BOHMIANA Y REALIDAD CUANTICA (2013)
Meaning, advantages, and disadvantages of nonrelativistic bohmian. quantum theory is investigated, based on a well-defined particle-path notion, affected by a target real field determining its quantum-mechanical behavior. This study is show with formal treatment for the motion of a particle described by a Gaussian wave packet in the case of free motion and motion in the presence of an even electric field.